Extragenital lichen sclerosus et atrophicus along the lines of Blaschko - Nilofar G Diwan; Pragya A Nair (Wolters Kluwer Medknow Publications, 2015)
Lichen sclerosus et atrophicus (LSA) is a chronic inflammatory dermatosis of unknown etiology. Extragenital involvement is uncommon and commonly affects the neck, shoulders, and upper portion of the trunk. It is predominant in women with a male-to-female ratio of 1:6 and occurs at any age. Linear pattern along the lines of Blaschko are seen. There is no cure for LSA. Topical corticosteroids and calcineurin inhibitors, such as tacrolimus, pimecrolimus, PUVA antimalarial agents, and topical retinoids have been tried with varying results. A case of a 33-year-old man with LSA over right lower limb along the lines of Blasckho is reported here.